Geomorphological Evidence of Active Faulting in Low Seismicity Regions—Examples From the Valley of Gobi Lakes, Southern Mongolia - van der Wal, Jorien L. N.; Nottebaum, V. C.; Stauch, G.; Binnie, S. A.; Batkhishig, O.; Lehmkuhl, F.; Reicherter, K. (Frontiers in Earth Science, 2021)
Active intraplate deformation as a far-field effect of the India-Eurasia convergence has led to four Mw~8 earthquakes in western and southern Mongolia in the past century. Palaeoseismological and morphotectonic studies have shown that these earthquakes are characteristic events along transpressive fault systems with cumulative offsets. The tectonically active Gobi Altai and Hangay mountains are separated by the seismically quiescent Valley of Gobi Lakes, which consists of major perennial rivers draining into endorheic lakes. Despite the scarcity of recorded earthquakes, Quaternary deposits in the Valley of Gobi Lakes are crosscut by multiple fault scarps with significant, landscape-altering displacements. To assess past earthquakes and the potential seismic hazard of this area, we apply remote sensing, tectono-morphometric techniques and cosmogenic nuclide dating to estimate the amount of deformation the faults in the Valley of Gobi Lakes are accommodating, and to determine the effect of these faults on local landscape evolution. The Tuyn Gol (gol = Mongolian for river) is crosscut by four E-W to NE-SW trending fault scarps that display variable fault kinematics due to scarp orientation differences relative to a stable NE-SW principle stress direction. Mapping of the >40-90 km long Valley of Gobi Lake faults shows that they can accommodate M~7 earthquakes. Offset measurements of the Tuyn Gol deposits allow Middle Pleistocene to modern vertical slip rate estimates and M~7 earthquake recurrence intervals of 0.012±0.007-0.13±0.07 mm/yr and 5.24±2.61-81.57±46.05 kyr, respectively. Cumulative vertical displacement amounts to 0.27±0.08 mm/yr, which is similar to that of major tectonic structures such as the Bogd fault in the Gobi Altai. This implies that the total active deformation accommodated by southern Mongolian faults may be larger than previously expected and distributed across more faults between the Hangay and the (Gobi) Altai mountain ranges. Geomorphological observations and surface exposure dating indicate that the Tuyn Gol drainage system developed over four to five 100 kyr climate cycles, during which active deformation played an important role in drainage reorganisation. Our results demonstrate the dominant role of tectonics on local landscape dynamics, indicating the importance of studying regional geomorphology to adequately estimate the earthquake potential of faults that were considered inactive.